INTERAKSI TIGA FAKTOR PUPUK TERHADAP PERTUMBUHAN DAN HASIL BAWANG PUTIH (Allium sativum L.) - Ardini Rahayunisa Homsa; Rifal Muhammad Sidiq; Syifa El Yanuar; Ardli Swardana; Hanny Hidayati Nafi'ah (Universitas 17 Agustus 1945 Samarinda, 2024)
Interaction of Three Fertilizer Factors on the Growth and Yield of Garlic (Allium sativum L.). Garlic is one of the potential commodities to be developed. One of the efforts to increase garlic production is to provide the nutrients needed. The purpose of this study was to examine the interaction between SP-18 fertilizer, ZA fertilizer and biofertilizer in increasing garlic growth and yield. The research method used is an experimental method with a Random Design Group of factorial patterns 3 x 2 x 3 repeated 2 times. Factor 1 is the dose of SP-18 (P) fertilizer which consists of 3 levels with doses: p1 (50 kg / ha), p2 (100 kg / ha), and p3 (150 kg / ha). Factor 2 is the dose of ZA (A) which consists of 2 levels with doses: a1 (225kg/ha) and a2 (300kg/ha). Factor 3 is the dose of biological fertilizer (H) which consists of 3 levels with doses: h0 (control), h1 (5 kg / ha), and h2 (10 kg / ha). The conclusion of this study is that there is an interaction between SP-18 fertilizer, ZA fertilizer and biofertilizer on garlic growth and yield. The best treatment combination is SP-18 150 kg/ha, ZA fertilizer 225 kg/ha and biofertilizer 10 kg/ha. Application of SP-18 fertilizer and ZA fertilizer can increase soil microbial activity characterized by increased garlic growth and yield.